Predisposing Factors that Affect the Early Detection of the Risk of Preeclampsia - Deasy Irawati; Siti Anisak; Ali Madinah (Health Notions, 2022)
Maternal mortality due to preeclampsia (PE) can be prevented by antenatal care and screening early detection of PE risk. The initial survey at the Bangkalan Health Center, 5 of pregnant women (63%) had risk factors for PE, but did not realize that their pregnancy was a risk for PE. The aim of this research is to explain the predispositing factors that influence the behavior of early detection of PE risk in pregnant women. This study was analytical observational study design with cross-sectional approach. The population were all pregnant women who visited Bangkalan Health Center. Sample size was 100 pregnant women, selected using cluster random sampling. Independent variables were  age, occupation, education, knowledge, attitudes; while dependent variable was early detection behavior of PE risk. Data were collected using questionnaire, then were analyzed using regression test. The variables that influence behavior were age (p = 0.002), knowledge (p = 0.005), and attitude (p = 0.000). The variables that had no effect were education and occupation. As conclusion; age, knowledge, and attitudes were predisposing factors of early detection behavior of PE risk. Keywords: preeclampsia; early detection; age; occupation; education; knowledge